Innovation in nursing health care practice: expansion of access in primary health care - Ingrid Margareth Voth Lowen; Aida Maris Peres; Carla da Ros; Paulo Poli Neto; Nilza Teresinha Faoro
ABSTRACT Objective: analyze the reorganization of the health care practice of nurses as an innovative strategy for expansion of access in primary care. Method: qualitative and quantitative study, which interviewed 32 management and care nurses and collected documentary data from public reports of production of nursing consultations from 2010 to 2014, in a municipality in southern Brazil. Data processing for textual analysis was performed by IRAMUTEQ software; for simple descriptive statistical analysis, the program Excel 2013 was used. Results: in the innovative care practice class, associated with awareness of change, related to implementation of the FHS, its challenges and advantages, the following subclasses were identified: reorganization of schedules, nursing consultation, physical restructuring of BHUs, and shared consultation. Final considerations: the need to expand access to and valorization of care practice encourages the development of innovative strategies. The protagonism of care needs to be discussed in the various spaces so that each professional carry out the respective role with competence and efficacy.